Catalytic material as well as preparation method and application thereof
By acid treatment of the negative electrode material of the used battery and reaction with titanium dioxide and inorganic alkali, high-performance catalytic materials were prepared, which solved the problem of poor performance of the negative electrode material in the used battery and achieved the effect of efficient degradation of organic pollutants.
Patent Information
- Application Number
- CN202411637857.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-18
AI Technical Summary
The negative electrode materials in waste lithium-ion batteries have poor performance and cannot be effectively utilized, and the prior art has conducted less research on its regeneration.
By performing the first acid treatment and solid-liquid separation of the negative electrode sheet of the used battery, the negative electrode material is obtained, and then mixed with titanium dioxide and inorganic alkali, and the second acid treatment is performed to finally prepare a catalytic material with excellent pore size and specific surface area.
The purity and performance of the negative electrode material in the used batteries are improved, so that the prepared catalytic material has a high pore capacity and specific surface area. When used to degrade organic pollutants, the organic degradation rate is high and the material loss is less.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalytic materials, and in particular relates to a catalytic material and a preparation method and use thereof. Background Art
[0002] With the booming electric vehicle market, a huge number of waste power batteries have been generated. Considering the pollution of hazardous waste to the environment and the scarcity of resources, the recycling of waste lithium-ion batteries has important economic value and practical significance. In recent years, the recycling of positive electrode materials (such as high-value metals such as cobalt, nickel and lithium) has made considerable progress, but the regeneration of negative electrode materials with lower added value (mainly graphite) has rarely been mentioned. However, the negative electrode materials in waste batteries currently have a series of poor properties such as pore size, specific surface area and purity, and cannot be effectively utilized. Summary of the invention
[0003] The purpose of the present invention is to provide a catalytic material and a preparation method and use thereof. The catalytic material prepared by the method provided by the present invention has excellent pore size and specific surface area and high purity. The catalytic material provided by the present invention has significant advantages in degrading organic pollutants, has a high organic matter degradation rate, and has little material loss after the reaction.
[0004] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a catalytic material, wherein the method comprises: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to a first acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing titanium dioxide, an inorganic base and the negative electrode material, reacting to obtain a mixed product; S3, subjecting the mixed product to a second acid treatment and collecting a solid phase product.
[0005] Optionally, the method further comprises: in step S2, titanium dioxide and an inorganic base are mixed and reacted for more than 2 hours, and then the negative electrode material is added and the reaction is continued for more than 2 hours to obtain the mixed product; Wherein, the reaction temperature is above 90°C, preferably 90-120°C; The inorganic base includes sodium hydroxide and / or potassium hydroxide, and the concentration of the inorganic base is 5-20%.
[0006] Optionally, the mass ratio of the titanium dioxide to the negative electrode material is (5-10):1.
[0007] Optionally, the waste battery is a battery whose negative electrode contains carbon material; The discharging comprises: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a mass concentration of more than 0.2 mol / L for more than 2 hours.
[0008] Optionally, the concentration of the first acid solution in the first acid treatment is above 4 mol / L; the first acid solution comprises an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid; The temperature of the first acid treatment is above 60°C, preferably 60-90°C; the time is above 1h, preferably 2-6h; The ratio of the volume of the first acid solution to the mass of the negative electrode is 4 or more.
[0009] Optionally, the concentration of the second acid solution in the second acid treatment is less than 2 mol / L; the second acid solution includes one or more of hydrochloric acid, nitric acid, sulfuric acid and perchloric acid; The temperature of the second acid treatment is above 60°C, preferably 60-90°C; the time is above 30 minutes, preferably 30-120 minutes; The mass ratio of the second acid solution to the mixed product is (5-20):1.
[0010] Optionally, the method further comprises: in step S3, after the second acid treatment, taking out the solid phase product, washing and drying it to obtain a catalytic material; The drying temperature is above 60° C. and the drying time is above 6 hours.
[0011] The second aspect of the present invention provides a catalytic material prepared by the method described in the first aspect of the present invention.
[0012] Optionally, the specific surface area of the catalytic material is 160 m 2 / g or more, pore volume is 0.65cm 3 / g or above.
[0013] The third aspect of the present invention provides use of the catalytic material described in the second aspect of the present invention in degrading organic pollutants.
[0014] Through the above technical scheme, the present invention performs a first acid treatment on the negative electrode sheet in the waste battery to obtain a negative electrode material, then mixes and reacts the negative electrode material, titanium dioxide and an inorganic base to obtain a mixed product, and then performs a second acid treatment on the mixed product to prepare a catalytic material. The method provided by the present invention can further improve the purity and performance of the negative electrode material in the waste battery, and mixes and reacts the negative electrode material with titanium dioxide and an inorganic base, so that the prepared catalytic material has excellent pore volume and specific surface area, high purity, and the catalytic material provided by the present invention has significant advantages in the degradation of organic pollutants, with a high organic matter degradation rate and less material loss after the reaction.
[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0016] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0017] A first aspect of the present disclosure provides a method for preparing a catalytic material, wherein the method comprises: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to a first acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing titanium dioxide, an inorganic base and the negative electrode material, reacting to obtain a mixed product; S3, subjecting the mixed product to a second acid treatment and collecting a solid phase product.
[0018] The method provided by the present invention can further improve the purity and performance of the negative electrode material in waste batteries, so that it is mixed and reacted with titanium dioxide and an inorganic base, so that the prepared catalytic material has excellent pore volume and specific surface area and high purity. The catalytic material provided by the present invention has significant advantages in using it to degrade organic pollutants, with a high organic matter degradation rate and little material loss after the reaction.
[0019] In the present disclosure, the negative electrode sheet obtained by disassembling in step S0 includes a negative electrode material and a current collector.
[0020] In a specific embodiment, the method further comprises: in step S2, titanium dioxide and an inorganic base are mixed and reacted for more than 2 hours, and then the negative electrode material is added, and the reaction is continued for more than 2 hours to obtain the mixed product; wherein the reaction temperature is above 90°C, preferably 90-120°C. In the above embodiment, the presence of sodium hydroxide provides an alkaline environment for the entire reaction system, effectively promotes the reaction between the negative electrode material, titanium dioxide and the inorganic base, and enables the reaction to proceed uniformly, so that the prepared catalytic material has higher stability and purity, and the prepared catalytic material has excellent pore volume and specific surface area. The catalytic material provided by the present disclosure has significant advantages in the degradation of organic pollutants, with a high organic matter degradation rate and less material loss after the reaction.
[0021] In a specific embodiment, the inorganic base includes sodium hydroxide and / or potassium hydroxide, preferably sodium hydroxide; the concentration of the inorganic base is 5-20%, preferably 8-15%.
[0022] In a specific embodiment, the mass ratio of titanium dioxide to the negative electrode material is (5-10): 1, preferably (5-8): 1. In the above embodiment, controlling the mass ratio of the titanium-containing compound to the negative electrode material within the preferred range of the present application can further improve the pore volume, specific surface area and purity of the catalytic material, and using it in the degradation of organic pollutants has more significant advantages, the organic matter degradation rate is further improved, and the material loss after the reaction is less.
[0023] In a specific embodiment, the waste battery is a battery whose negative electrode contains carbon material.
[0024] In a specific embodiment, the discharging comprises: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a mass concentration of 0.2 mol / L or more for more than 2 hours.
[0025] In a specific embodiment, the concentration of the first acid solution in the first acid treatment is 4 mol / L or more, preferably 5 to 8 mol / L. In the above embodiment, controlling the concentration of the acid solution in the first acid treatment within the preferred range of the present application can further improve the performance of the prepared material.
[0026] In a specific embodiment, the first acid solution includes an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid.
[0027] In a specific embodiment, the temperature of the first acid treatment is above 60° C., preferably 60-90° C.; and the time is above 1 h, preferably 2-6 h.
[0028] In a specific embodiment, the ratio of the volume of the first acid solution to the mass of the negative electrode material is greater than 4, preferably 6 to 12. In the above embodiment, controlling the mass ratio of the first acid solution to the negative electrode within the preferred range of the present application can further improve the performance of the prepared material.
[0029] In a specific embodiment, the concentration of the second acid solution in the second acid treatment is 2 mol / L or less, preferably 0.1 to 1 mol / L. In the above embodiment, controlling the concentration of the acid solution in the second acid treatment within the preferred range of the present application can further improve the performance of the prepared material.
[0030] In a specific embodiment, the second acid solution includes one or more of hydrochloric acid, nitric acid, sulfuric acid and perchloric acid.
[0031] In a specific embodiment, the temperature of the second acid treatment is above 60° C., preferably 60-90° C.; the time is above 30 min, preferably 30-120 min.
[0032] In a specific embodiment, the ratio of the volume of the second acid solution to the mass of the mixed product is (5-20): 1, preferably (6-12): 1. In the above embodiment, controlling the mass ratio of the second acid solution to the mixed product within the preferred range of the present application can further improve the performance of the prepared material.
[0033] In a specific embodiment, the method further includes: in step S3, after the second acid treatment, taking out the solid phase product, washing and drying it to obtain a catalytic material; the drying temperature is above 60°C, preferably 70-90°C; the drying time is above 6 hours, preferably 18-36 hours.
[0034] The second aspect of the present invention provides a catalytic material prepared by the method described in the first aspect of the present invention.
[0035] In a specific embodiment, the specific surface area of the catalytic material is 160 m 2 / g or more, pore volume is 0.65cm 3 / g or more, preferably, the specific surface area of the catalytic material is 175m 2 / g or more, pore volume is 0.8cm 3 / g or above.
[0036] The third aspect of the present disclosure provides use of the catalytic material described in the second aspect of the present invention in degrading organic pollutants.
[0037] The catalytic material provided by the present disclosure has excellent pore volume and specific surface area, and high purity. The catalytic material provided by the present disclosure has significant advantages in being used to degrade organic pollutants, with a high organic matter degradation rate and little material loss after the reaction.
[0038] The present invention is further described below by way of examples, but the present invention is not limited thereby. The raw materials used in the examples and comparative examples can be obtained through commercial channels.
[0039] Example 1 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 2 mol / L for 4 hours for discharge, and then disassemble them to obtain the negative electrode sheet.
[0040] b. Subject the negative electrode sheet in step a to a first acid treatment, and then perform solid-liquid separation, and then wash the solid phase with ethylene glycol to obtain a negative electrode material; wherein the concentration of the first acid solution in the first acid treatment is 6 mol / L, the first acid solution is a nitric acid solution, and the ratio of the volume of the first acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 hours.
[0041] c. Mix titanium dioxide and the inorganic alkali solution and react for 2 hours, then add the negative electrode material in step b, and continue to react for 4 hours to obtain a mixed product; wherein the inorganic base is sodium hydroxide, the concentration of the inorganic alkali solution is 10%, the mass ratio of titanium dioxide to the negative electrode material is 6:1, and the reaction temperature is 110°C.
[0042] d. Subjecting the mixed product to a second acid treatment, taking out the solid phase product, washing it with ethanol, and then drying it to obtain a catalytic material; wherein the concentration of the second acid solution in the second acid treatment is 0.2 mol / L, the second acid solution is a hydrochloric acid solution, the temperature of the second acid treatment is 90°C, and the mass ratio of the second acid solution to the mixed product is 10:1; the acid treatment time is 90 min, the drying temperature is 80°C, and the drying time is 24 h.
[0043] Example 2 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 3 mol / L, soak for 4 hours for discharge, and then disassemble to obtain the negative electrode sheet.
[0044] b. Subject the negative electrode sheet in step a to a first acid treatment, and then perform solid-liquid separation, and then wash the solid phase with ethylene glycol to obtain a negative electrode material; wherein the concentration of the first acid solution in the first acid treatment is 5 mol / L, the first acid solution is a sulfuric acid solution, and the ratio of the volume of the first acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 hours.
[0045] c. Mix titanium dioxide and the inorganic alkali solution and react for 2 hours, then add the negative electrode material in step b, and continue to react for 4 hours to obtain a mixed product; wherein the inorganic base is sodium hydroxide, the concentration of the inorganic alkali solution is 20%, the mass ratio of titanium dioxide to the negative electrode material is 6:1, and the reaction temperature is 100°C.
[0046] d. Subjecting the mixed product to a second acid treatment, taking out the solid phase product, washing it with ethanol, and then drying it to obtain a catalytic material; wherein the concentration of the second acid solution in the second acid treatment is 0.2 mol / L, the second acid solution is a hydrochloric acid solution, the temperature of the second acid treatment is 90°C, and the mass ratio of the second acid solution to the mixed product is 10:1; the acid treatment time is 90 min, the drying temperature is 80°C, and the drying time is 20 h.
[0047] Example 3 a. Immerse the conventional commercially available waste lithium batteries in a sodium chloride solution with a mass concentration of 2 mol / L for 4 hours for discharge, and then disassemble them to obtain the negative electrode sheet.
[0048] b. Subject the negative electrode sheet in step a to a first acid treatment, and then perform solid-liquid separation, and then wash the solid phase with ethylene glycol to obtain a negative electrode material; wherein the concentration of the first acid solution in the first acid treatment is 6 mol / L, the first acid solution is a nitric acid solution, and the ratio of the volume of the first acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 hours.
[0049] c. Mix the titanium-containing compound and the inorganic alkali solution and react for 2 hours, then add the negative electrode material in step b, and continue to react for 4 hours to obtain a mixed product; wherein the inorganic base is potassium hydroxide, the concentration of the inorganic alkali solution is 10%, the mass ratio of titanium dioxide to the negative electrode material is 9:1, and the reaction temperature is 100°C.
[0050] d. Subjecting the mixed product to a second acid treatment, taking out the solid phase product, washing it with ethanol, and then drying it to obtain a catalytic material; wherein the concentration of the second acid solution in the second acid treatment is 0.2 mol / L, the second acid solution is a nitric acid solution, the temperature of the second acid treatment is 90° C., and the mass ratio of the second acid solution to the mixed product is 10:1; the time for the acid treatment is 90 min, the drying temperature is 80° C., and the drying time is 24 h.
[0051] Comparative Example 1 The method of Example 1 is adopted, except that step b is not performed.
[0052] Comparative Example 2 The method of Example 1 is adopted, except that in step c, titanium dioxide is mixed with the negative electrode material in step b and reacted for 4 hours to obtain a mixed product.
[0053] Comparative Example 3 a. Immerse conventional waste lithium batteries in a sodium chloride solution with a mass concentration of 2 mol / L, soak for 4 hours for discharge, and then disassemble them to obtain the negative electrode sheet.
[0054] b. Treat the negative electrode sheet in step a with acid, perform solid-liquid separation, and then wash the solid phase with ethylene glycol to obtain a negative electrode material; wherein the concentration of the acid solution in the acid treatment is 6 mol / L, the acid solution is a nitric acid solution, and the ratio of the volume of the acid solution to the mass of the negative electrode is 10:1; the temperature of the acid treatment is 90° C., and the time of the acid treatment is 4 hours.
[0055] c. Mix titanium dioxide and the inorganic alkali solution and react for 2 hours, then add the negative electrode material in step b, continue to react for 4 hours to obtain a mixed product, filter and recover the solid phase product, wash and dry the solid phase product to obtain a catalytic material; wherein the inorganic base is sodium hydroxide, the concentration of the inorganic alkali solution is 10%, the mass ratio of titanium dioxide to the negative electrode material is 6:1, the reaction temperature is 110°C, the drying temperature is 80°C, and the drying time is 24 hours.
[0056] Test Case The catalytic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested in the following manner: The warm nitrogen adsorption-desorption test (BET) was carried out on a JW-BK200C surface area and pore volume analyzer produced by Beijing Jingwei Gaobo Co., Ltd. The surface area and pore volume were calculated using the two-parameter BET equation.
[0057] A certain volume of methyl orange solution (with a concentration of 20 mg / L) was placed in a reactor, and the amount of the catalytic material provided in Examples 1 to 3 and Comparative Examples 1 to 3 was 1 g / L. The reaction was carried out under irradiation with a 300 W xenon lamp. After the reaction lasted for 60 minutes, a certain amount of the reaction solution was taken and centrifuged. Then, a spectrophotometer was used to measure the absorbance of the sample after centrifugation at the maximum absorption wavelength (466 nm) of methyl orange, and a standard curve of methyl orange was drawn. The sample concentration was calculated based on the absorbance.
[0058] Organic matter degradation rate = (C0-C t ) / C0×100%; where C0 is the initial concentration of methyl orange solution, C t is the concentration of methyl orange solution after the reaction; Material loss rate = (m0-m t ) / m0×100%; where m0 is the initial mass of the catalytic material, m t is the mass of the catalytic material after the reaction. The results are shown in Table 1.
[0059] Table 1
[0060] As can be seen from Table 1, the method provided in the present application can further improve the purity and performance of the negative electrode material in the waste battery, so that it is mixed and reacted with titanium dioxide and an inorganic base, and the prepared catalytic material can have excellent pore volume and specific surface area, and high purity. The catalytic materials provided in Examples 1 to 3 of the present application have significant advantages in degrading organic pollutants, and the organic matter degradation rate is high, which can reach more than 94%, and the material loss after the reaction is small, which can reach less than 6%.
[0061] By comparing Comparative Example 1 with Example 1, it can be seen that since Comparative Example 1 did not perform the first acid treatment, the pore volume and specific surface area of the prepared catalytic material decreased. When the catalytic material provided in Comparative Example 1 was used to degrade organic pollutants, the organic matter degradation rate was significantly lower than that of the examples of the present application, while the material loss rate was significantly higher than that of Examples 1 to 3 of the present application.
[0062] By comparing Comparative Example 2 with Example 1, it can be seen that since Comparative Example 2 is not subjected to alkali treatment, the reaction cannot be promoted in the positive direction, which reduces the reaction efficiency, thereby causing the pore volume and specific surface area of the prepared catalytic material to decrease. When the catalytic material provided in Comparative Example 2 is used to degrade organic pollutants, the organic matter degradation rate is significantly lower than that of the examples of the present application, while the material loss rate is significantly higher than that of Examples 1 to 3 of the present application.
[0063] By comparing Comparative Example 3 with Example 1, it can be seen that since Comparative Example 3 did not perform the second acid treatment, the pore volume and specific surface area of the prepared catalytic material decreased. When the catalytic material provided in Comparative Example 3 was used to degrade organic pollutants, the organic matter degradation rate was significantly lower than that of the examples of the present application, while the material loss rate was significantly higher than that of Examples 1 to 3 of the present application.
[0064] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0065] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0066] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a catalytic material, wherein: The method includes: S0, discharging and disassembling the waste battery to obtain the negative electrode sheet; S1, subjecting the negative electrode sheet to a first acid treatment, and then performing solid-liquid separation to obtain a negative electrode material; S2, mixing titanium dioxide, an inorganic base and the negative electrode material, reacting to obtain a mixed product; S3, subjecting the mixed product to a second acid treatment and collecting a solid phase product.
2. The method according to claim 1, wherein: The method further comprises: in step S2, titanium dioxide and an inorganic base are mixed and reacted for more than 2 hours, and then the negative electrode material is added and the reaction is continued for more than 2 hours to obtain the mixed product; Wherein, the reaction temperature is above 90°C, preferably 90-120°C; The inorganic base includes sodium hydroxide and / or potassium hydroxide, and the concentration of the inorganic base is 5-20%.
3. The method according to claim 2, wherein: The mass ratio of the titanium dioxide to the negative electrode material is (5-10):
1.
4. The method according to claim 1, wherein: The waste battery is a battery whose negative electrode contains carbon material; The discharging comprises: immersing the waste battery in a sodium chloride or sodium sulfate aqueous solution with a mass concentration of more than 0.2 mol / L for more than 2 hours.
5. The method according to claim 1, wherein: The concentration of the first acid solution in the first acid treatment is 4 mol / L or more; the first acid solution comprises an oxygen-containing acid, preferably one or more of nitric acid, sulfuric acid and perchloric acid; The temperature of the first acid treatment is above 60°C, preferably 60-90°C; the time is above 1h, preferably 2-6h; The ratio of the volume of the first acid solution to the mass of the negative electrode is 4 or more.
6. The method according to claim 1, wherein: The concentration of the second acid solution in the second acid treatment is less than 2 mol / L; the second acid solution includes one or more of hydrochloric acid, nitric acid, sulfuric acid and perchloric acid; The temperature of the second acid treatment is above 60°C, preferably 60-90°C; the time is above 30 minutes, preferably 30-120 minutes; The mass ratio of the second acid solution to the mixed product is (5-20):
1.
7. The method according to claim 1, wherein: The method further comprises: in step S3, after the second acid treatment, taking out the solid phase product, washing and drying it to obtain a catalytic material; The drying temperature is above 60° C. and the drying time is above 6 hours.
8. A catalytic material prepared by the method according to any one of claims 1 to 7.
9. The catalytic material according to claim 8, wherein The specific surface area of the catalytic material is 160 m 2 / g or more, pore volume is 0.65cm 3 / g or above.
10. Use of the catalytic material according to claim 8 or 9 in degrading organic pollutants.